The Effect of Avocado Oil Cream on Accelerating Wound Healing Process: A Macroscopic Analysis - Amalia, Fia; Paramanandi, Dini Agusti; Monica, Yelis Tria (Universitas Brawijaya, 2025)
Wound healing is a complex physiological process involving hemostasis, inflammatory, proliferative and remodelling phases. Natural compounds such as avocado (Persea americana) oil, rich in oleic and linoleic acids, have shown potential in supporting tissue regeneration. This study aimed to analyse the macroscopic wound healing effects of avocado oil cream at different concentrations in mice. Eighteen male Swiss Webster mice (8 weeks old, 30 g) were divided into three groups: K (0%) as a control group, P1 (25%) and P2 (50%) as the treatment groups. A 6 mm excisional wound was created on each mouse, and cream was applied once daily for seven days. Wound area and contraction were measured on days 1-7 using a digital calliper and analysed using one-way ANOVA (p>0.05). Results showed a consistent decrease in wound area and an increase in wound contraction across all groups, indicating progressive healing. Although statistical differences were not significant (p>0.05), the P2 (50%) group demonstrated a faster rate of wound area reduction and higher contraction compared to other groups. Macroscopically, P2 (50%) wound exhibited cleaner surfaces, earlier granulation tissue formation, and better epithelial coverage. These effects are likely related to the bioactive properties of avocado oil, which modulate inflammation, stimulate fibroblast proliferation, and enhance collagen remodelling. In conclusion, the topical application of avocado oil cream, particularly at a 50% concentration, showed promising macroscopic improvement in wound healing. Further studies with longer observation periods and histological analysis are recommended to confirm its therapeutic potential.